Entotourism potential in Sabah, Malaysia: A Tourists’ perspective - Gao Le; Ak Mohd Rafiq Ak Matusin; Kalsum M. Yusah; Nor Akmar Abdul Aziz; Awangku Hassanal Bahar Pengiran Bagul; Nordiana Mohd. Nordin; Mahadimenakbar Mohamed Dawood; Fiffy Hanisdah Saikim (Cogent OA, 2021)
In favor of the Big Five Invertebrates form the basis for ecosystem functioning but are typically neglected in ecotourism activities. Entotourism is introduced to elevate awareness about the potential of invertebrates and their conservation activity through tourism. Improved awareness via tourism activity can potentially lead to improved conservation practices. Yet, do tourists accept entotourism as another product of ecotourism? This study aims to determine the perception of tourists on entotourism activity in Sabah. We are implementing a mixed-method to acquire information needed via questionnaire surveys and in-depth interviews. At the same time, we applied a random sampling technique to gain the respective respondents. Data analysis used a t-test to examine gender perception and presented via Spider-Web configuration. In comparison, we used content analysis via Leximancer for qualitative analysis. This study demonstrated that people have a slightly different perception of insects and awareness based on their gender. Results show that most participants responded positively to insect information, awareness and their interest in certain insects. Respondents also gave their support to entotourism, which provided them with some new knowledge about insects. The interview has also indicated a positive perception of invertebrate information as part of the entotourism concept included in ecotourism activity. In conclusion, tourists’ perception of entotourism activity unveils a significant potential for the inclusion of invertebrate into current and future ecotourism activity, especially in Sabah. Alternately, it can be applied as a preparatory step for better planning and execution of invertebrate’s conservation and entotourism activity.